2003
DOI: 10.1016/s1352-2310(03)00500-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic signature of daily sampled urban atmospheric particles

Abstract: The magnetic signature of two sets of daily-sampled particulate matter (PM) collected in Munich, Germany, were examined and compared to variations in other pollution data and meteorological data using principal component analysis. The magnetic signature arising from the magnetic minerals in the PM, was examined using a fast and highly sensitive magnetic remanence measurement. The longest data set studied was 160 days, significantly longer than that of similar magnetic PM studies improving the statistical robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 25 publications
5
57
1
Order By: Relevance
“…Measurement of magnetic susceptibility or saturation isothermal remanent magnetization (SIRM) is a relatively new method to determine foliar-deposited aerosols in urban vegetation (Hofman et al 2014;Kardel et al 2011;Matzka and Maher 1999;Sant'Ovaia et al 2012;Urbat et al 2004). This technique has demonstrated that metallic PM 2.5 from road and rail traffic, including fuel combustion, brake abrasion, and corrosion, is deposited to leaves and may become embedded in them (Hofman et al 2014;Muxworthy et al 2003;Urbat et al 2004). SIRM of urban tree leaves has proven to be a good estimator of trafficderived aerosol (Kardel et al 2011;Maher et al 2013;Rai 2013).…”
Section: Quantification Of Deposited Aerosolsmentioning
confidence: 99%
“…Measurement of magnetic susceptibility or saturation isothermal remanent magnetization (SIRM) is a relatively new method to determine foliar-deposited aerosols in urban vegetation (Hofman et al 2014;Kardel et al 2011;Matzka and Maher 1999;Sant'Ovaia et al 2012;Urbat et al 2004). This technique has demonstrated that metallic PM 2.5 from road and rail traffic, including fuel combustion, brake abrasion, and corrosion, is deposited to leaves and may become embedded in them (Hofman et al 2014;Muxworthy et al 2003;Urbat et al 2004). SIRM of urban tree leaves has proven to be a good estimator of trafficderived aerosol (Kardel et al 2011;Maher et al 2013;Rai 2013).…”
Section: Quantification Of Deposited Aerosolsmentioning
confidence: 99%
“…Magnetic susceptibility (v) indicates the concentration of ferrimagnetic grains within a sample and is a suitable proxy for PM 10 concentration (Muxworthy et al 2003). A Bartington (Oxford, England) MS2B dual-frequency susceptibility sensor, connected to a MS2 susceptibility meter, was used according to Dearing (1999).…”
Section: Mineral Magnetic Analysismentioning
confidence: 99%
“…Iron impurities are often found in combustibles and can convert to iron oxides, such as magnetite or hematite, depending of the burning conditions (Muxworthy et al 2003), but they can also be related to the presence of ferrocene as a fuel additive (Braun et al 2006). That is why several studies have revealed large concentrations of iron in anthropogenic particulate matter (generally between 5 and 15%) and magnetite was identified as the dominant magnetic phase of Fe-rich particles (e.g.…”
Section: Discussionmentioning
confidence: 99%